PENERAPAN METODE DISKUSI INFORMASI DALAM PEMBELAJARAN PKn UNTUK MENUMBUHKAN MOTIVASI BELAJAR SISWA KELAS VI SEKOLAH DASAR - Wirahayu, Prapti (Jurnal Pendidikan Dasar, 2017)
Abstract: The Government through the Ministry of Education and Culture continues to monitor andimprove the weaknesses found in the national education.Based on the observations of investigatorsincluding teaching and learning in SDN Pohwates I still showing low result, it is because the studentshavingless motivation in learning, methods that are less suited to the child's condition, and also theinadequate environment. So it needs to find a learning method that can generate motivation andinterest of students in the classroom. With a fun method students can play an active role in thelearning process that increasethe learning outcomes. It can be done by various method, one of themare Discussion of Information Method.This study aims to determine student’s motivation on thesubjects of Citizenship Education after the applied methods Discussion of Information.This researchwas conducted in primary school of SD Negeri Pohwates I at 2016/2017 academic year, in the firstsemester of the sixth grade consist of 10 students. Where researchers perform duties as teachers ofsixth grade as well as the principal. Materials studied in this research is System of GovernmentAffairs from Civics. This study was conducted over 2 months, October to November 2016. ThroughDiscussion of Information, the influence on motivation and student achievement through students' test results are cycles prior to the study were: 64.0, Cycle 1 were: 73.0 and cycle 2 is: 85.0 (very good). Keywords: methods discussion of Information, learning motivation Abstrak: Penelitian ini bertujuan untuk mengetahui motivasi belajar siswa kelas VI SD NegeriPohwates I Kecamatan Kepohbaru Kabupaten Bojonegoro tahun pelajaran 2016/2017 pada matapelajaran Pendidikan Kewarganegaraan setelah diterapkan metode Diskusi Informasi.Penelitian initepatnya dilakukan di SD Negeri Pohwates I Kecamatan Kepohbaru Kabupaten Bojonegoro tahunpelajaran 2016/2017, pada siswa kelas VI semester I yang berjumlah 10 siswa. Dimana penelitimelaksanakan tugas sebagai guru pengajar kelas VI serta sebagai Kepala Sekolah. Materi yangdipelajari pada penelitian ini adalah mata pelajaran PKn pokok bahasan Sistem Pemerintahan RI.Penelitian ini dilaksanakan selama 2 bulan yaitu bulan Oktober sampai bulan Nopember 2016.Melalui kegiatan Diskusi Informasi berpengaruh pada motivasi dan prestasi belajar siswa melaluihasil tes belajar siswa yaitu siklus sebelum penelitian adalah : 64,0, siklus 1 adalah : 73,0 dan siklus 2adalah : 85,0 (sangat baik). Kata kunci: diskusi informasi, motivasi belajar.